Analysis of Badminton Athletes Anxiety Levels Before the Match - Ajining Putra, Dimas Frada; Suratman, Suratman (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the level of anxiety of badminton athletes of the Tugu Muda Semarang badminton club before the match. Anxiety is one of the psychological factors that can affect an athlete's performance, especially when facing competitive situations. This study uses a quantitative descriptive approach with a survey method. The sample consisted of 30 athletes in the U-13 and U-15 age groups, both male and female. The instrument used was the State-Trait Anxiety Inventory (STAI) questionnaire. The results showed that the average level of anxiety of athletes before the match was 59.79%, which is categorised as severe anxiety. Of the total respondents, 17 athletes (57%) experienced severe anxiety, 8 athletes (27%) had moderate anxiety, 4 athletes (13%) had mild anxiety, and 1 athlete (3%) did not experience anxiety. High anxiety is influenced by pressure to win, expectations of coaches or parents, and fear of failure. This condition can reduce the focus, self-confidence, and emotional stability of athletes. Therefore, psychological interventions such as progressive muscle relaxation and supportive counselling are needed to help reduce anxiety and improve mental readiness. The results of this study are expected to be the basis for the preparation of a more comprehensive training program, including mental aspects. In conclusion, attention to the psychological condition of athletes is important to support optimal performance, especially in dealing with pressure during competition.